Description of Grade VII Students'Concept Understanding on Set Topic - Miftahul Rezki; Ronal Rifandi; Fridgo Tasman; Veggi Yokri; Yerizon (Rangkiang Mathematics Journal, 2022)
This research has the aims to explain about the understanding of students mathematical concepts on set topic. This research is a descriptive research whose population is 7th grade students with a sample of 94 students. The instrument used in this research is a test question regarding the set material which contains indicators of mathematics conceptual understanding. The result of the test analysis show that as many as of students with exellent concept understanding, of students with good concept category, of students with sufficient category, of students with low concept criteria, and of students with most low concept understanding criteria.